PENGARUH PENDAPATAN, SUKU BUNGA, DAN UANG MUKA TERHADAP PERMINTAAN KREDIT PEMILIKAN RUMAH DI KOTA PONTIANAK - B61112006, VIORITA ZULVIANTI (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT Bank lending to the consumer sector has increased dramatically since the economic crisis hit Indonesia ten years ago. Banks realize that the opportunities in the greater consumer market, where the risk of facing a relatively smaller than a credit on the investment market. There are several types of consumer sector financed with loans by the Bank, one of which is the housing sector through housing loan. This research focuses to examine and analyze how the influence of the income of customer, Interest Rate and down payment on Demand Housing Loan. The research methodology used form of causality research is to analyze the causal relationship between the variables of the study in accordance with the hypothesis that drafted. Sampling techniques using cross section data is the method of data on one or more variables collected at a particular time, collecting data using questionnaires and interviews. For analysis techniques using statistical testing with multiple regression test. The results of this study are income of customer variable, interest rate and advances together (simultaneously) affect the level of demand for housing loan. Income positive effect on demand for housing loan, interest rates and down payment significant negative effect on the demand for housing loan. Key words : Income of Customer, Interest Rate, Down Payment and Demand of Housing Loan Â  Â